PERAN REMAJA MEMBANGUN BANGSABEBAS NARKOBA - Fakhri Nur Faisal; Edy Soesanto, Alwi Sihab, Alwi Zidan (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The drug problem in Indonesia is still something that is urgent and complex. In the last decade this problem has become widespread. This is proven by the significant increase in the number of drug abusers or addicts, along with the increasing disclosure of drug crime cases with increasingly diverse patterns and increasingly massive syndicate networks. Indonesian society, and even the world community in general, is currently facing a very worrying situation due to the widespread use of various types of illegal drugs. This concern is increasingly sharpened due to the rampant illicit trafficking of narcotics which has spread to all levels of society, including among the younger generation. This will greatly influence the life of the nation and state in the future. The behavior of some teenagers who have clearly ignored the values, norms and laws that apply in society is one of the causes of widespread drug use among the younger generation. In everyday life in society, there are still many teenagers who still abuse drugs.